First record and two new species of the genus Limonius Eschscholtz (Coleoptera, Elateridae, Dendrometrinae) from Taiwan - Arimoto, Kôichi; Suzuki, Wataru (Zootaxa, 2020)
Limonius sapphirus sp. n. and L. onyx sp. n. are described from Taiwan, representing the first record of the genus Limonius in Taiwan. We provide an updated key to the genera of the subtribe Athouina in Taiwan and general morphological information of L. eximius Lewis, 1894 and L. ignicollis Lewis, 1894, which are endemic to Japan, for comparison with the two Taiwanese species. We believe that the two Taiwanese species and L. ignicollis are closely allied, sharing morphological characteristics of the lateral carina of prothorax, prosternal spine and aedeagus.